Formulações de Beauveria bassiana no controle de Thaumastocoris peregrinus Carpintero & Dellapé, (Hemiptera: Thaumastocoridae) e isolamento de fungos entomopatogênicos e endofíticos em plantios de eucalipto - Tedesco, Flavia Galvan (2018)
This work aimed to evaluate the potential insecticide of Beauveria bassiana on the eucalyptus bronze bug, Thaumastocoris peregrinus, to collect, identify and molecularly characterize entomopathogenic and endophytic fungi from eucalyptus plantations. In the first bioassay B. bassiana was tested in different formulations on adults and 3rd instar nymphs of T. peregrinus. For the second bioassay, the most virulent B. bassiana formulation was tested at different (1,0×108; 0,5×108; 1,0×107; 0,5×107; 1,0×106; 0,5×106 conídios mL-1)on T. peregrinus adults. For the third bioassay the formulations of B. bassiana were tested for the ability to activate the metabolic routes, being carried out of phytoalexins and Fal. The fourth bioassay was from soil collections in five eucalyptus plantations. The fungi developed were submitted to molecular analysis using the ISSRPCR technique, with the CCA, CGA and CT primers. The ITS technique with ITS1 and ITS4 primers and DNA sequencing of fungi were also used. The fifth bioassay was performed from eucalyptus leaves collected from the same stands in which soil samples were collected, in order to find endophytic fungi. Endophytic fungi were also subjected to molecular analysis using the ISSR-PCR technique with primers EF1-728F, EF1-986R, (EF1a) T1 and Bt-2b. Then the ITS technique was performed with the ITS1 and ITS4 primers and DNA sequencing of the fungi. In the first bioassay the treatments / formulations T1 and T2, which caused mortality of 94% and 92%, respectively, of adults of T. peregrinus are highlighted. For T. peregrinus 3rd instar nymphs T1, T2 and T4 treatments caused 100%, 100% and 84% mortality, respectively. In the second bioassay, the concentrations that caused the highest adult mortality of T. peregrinus were 1,0×108; 0,5×108; 1,0×107; 1,0×106; 0,5×106 that differed statistically from the concentration 0.5×107 and the control. In the resistance induction bioassay the T2 treatment differed from the other treatments and from the control, presenting a value of 0.3316 for phytoalexins and 0.0674 for Fal. In the soil samples collected from eucalyptus plantations, 15 isolates of possible entomopathogenic fungi were found, with the ISSRPCR analysis it was possible to obtain amplification results with the three primers appointed. Phylogenetic analysis of entomopathogenic fungi divided these into three different genera, Penicillium, Mortierella and Purpureocillium. In the eucalyptus leaves were also found 15 isolates of possible endophytic fungi, with the ISSR-PCR analysis it was possible to obtain amplification results with the primers used. With phylogenetic analysis of these fungi, three genera were identified: Aspergillus, Botrysphaeria and Neofusicoccum. It should be noted that the entomopathogenic B. bassiana fungus presents potential for T. peregrinus control and also has potential as an inducer of resistance. With the molecular identification of the fungi found in the soil samples, and in the leaves it was verified that the eucalyptus crop, can present microorganisms that have potential as controllers of insects and diseases.